2017
DOI: 10.1111/pcn.12609
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal separation and antidepressant drug on epigenetic regulation of the brain‐derived neurotrophic factor exon I promoter in the adult rat hippocampus

Abstract: These findings indicate that MS induced epigenetic changes at the BDNF exon I promoter and these changes were prevented by antidepressant drug treatment during adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 75 publications
1
26
1
Order By: Relevance
“…In our study, we observed that rats were subjected to MS every 3 h per day from PDN 1 to 21, and the immobility time increased when rats became adults [ 23 ]. We also showed that brain-derived neurotrophic factor (BDNF) and GR are involved in this mechanism, similar to previous studies [ 7 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, we observed that rats were subjected to MS every 3 h per day from PDN 1 to 21, and the immobility time increased when rats became adults [ 23 ]. We also showed that brain-derived neurotrophic factor (BDNF) and GR are involved in this mechanism, similar to previous studies [ 7 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…The ChIP assay was used from the SimpleChIP ® Plus Enzymatic Chromatic IP kit (#9005, Cell Signaling, Beverly, MA, USA) according to the manufacturer’s instructions and as described previously [ 7 , 23 , 24 ]. Briefly, the DNA-protein of hippocampal tissue was crosslinked with 1.5% formaldehyde for 20 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…MS stress occurring in the early phase of life can dramatically disrupt brain development and hence induce long-term changes, which may be the reason for the age-dependent effect of MS. Moreover, some studies report increased BDNF and decreased BDNF response to MS in the hippocampus and mPFC of rodents, respectively [68,69]; however, others do not [70,71]. The contradictory results may be related to the age of the animal as well as the duration of stress.…”
Section: Maternal Separationmentioning
confidence: 99%
“…It is also worth noting that recent studies based on animal models indicate positive effects of antidepressants which eliminate negative effects of epigenetic mechanisms [78,79]. However, as we mentioned earlier, the results of the research conducted so far are not clear.…”
Section: Oxytocin: Social Neuropeptide?mentioning
confidence: 89%